KONSEP KEPEMILIKAN RUMAH BAGI WARGA NEGARA ASING DALAM RANGKA PERCEPATAN PENINGKATAN INVESTASI DI INDONESIA - Roestamy, Martin (DERECHTSSTAAT, 2016)
ABSTRACTIndonesia is known to have a good resource potential. Nevertheless, it has turned out it is not enough to attract investors. All that should be coupled with the ease of the procedure, the availability of law and good services to investors. This study attempted to correlate between the governments policies of home ownership for foreign with efforts to increase investment. It is expected to be answered on how the residential home ownership for foreigners in Indonesia? and how the concept of home ownership for foreigners in order to accelerate the increase in investment in Indonesia ?. using scientific principles the results of this study explained that the application of positive law pertaining to houses and buildings have ignored the principle of horizontal separation adopted in BAL and customary law, in practice the ownership of homes and buildings tend to use the principle of sticking always attach rights to land with the house or building that is on it, this has resulted in WNA difficult to get home because the houses built over the right to use is limited. To overcome this problem needs to be realized registration of houses and buildings by awarding certificate proof of right to a home or building or property that can be transferred, charged to a right of material, to realize the ideals Article 8 UUBG by Presidential Decree as mandated in Article 12 paragraph 4 of the Indonesian Government Regulation No. 36 Year 2005 concerning the Implementing Regulations of Law BG. Thus the application of the principle of horizontal separation adopted in BAL and customary law, in practice the ownership of homes and buildings will allow foreigners have a house to attract foreign investment to invest in Indonesia. Finally with the ease is expected to have an impact on increased investment in Indonesia until this is less good, especially when compared with neighboring countries.